2016
DOI: 10.1002/tea.21318
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing biological data in museums: Visitor learning with an interactive tree of life exhibit

Abstract: In this study, we investigate museum visitor learning and engagement at an interactive visualization of an evolutionary tree of life consisting of over 70,000 species. The study was conducted at two natural history museums where visitors collaboratively explored the tree of life using direct touch gestures on a multi-touch tabletop display. In the study, 247 youth, aged 8-15 years, were randomly assigned in pairs to one of four conditions. In two of the conditions, pairs of youth interacted with different vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…In addition, exhibit evaluations have documented museum visitors' challenges deciphering color in visualizations ranging from nanoscale structures to ocean satellite imagery; visitors have been found to link colors to temperature despite design intentions [10], [11]. Aside from these studies related to decoding, most published work on visualizations of large scientific datasets have focused on explicating design considerations particular to the museum context [3], [12], looking at patterns of collaboration at these visualizations [13], and describing the nature of learning [2], all of which contributes to our understanding of how visitors use visualizations in settings of informal learning. To our knowledge, this study represents the first detailed analysis of visitors' decoding process as they use a visualization in an informal learning context.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, exhibit evaluations have documented museum visitors' challenges deciphering color in visualizations ranging from nanoscale structures to ocean satellite imagery; visitors have been found to link colors to temperature despite design intentions [10], [11]. Aside from these studies related to decoding, most published work on visualizations of large scientific datasets have focused on explicating design considerations particular to the museum context [3], [12], looking at patterns of collaboration at these visualizations [13], and describing the nature of learning [2], all of which contributes to our understanding of how visitors use visualizations in settings of informal learning. To our knowledge, this study represents the first detailed analysis of visitors' decoding process as they use a visualization in an informal learning context.…”
Section: 2mentioning
confidence: 99%
“…These visualizations provide informal learners an opportunity to engage with critical new areas of science and foster important data literacy skills. Recent projects include the National Oceanic and Atmospheric Administration's (NOAA's) Science on a Sphere program, which visualizes environmental data on a spherical display [1]; the DeepTree exhibit, which allows visitors to interact with and explore an evolutionary tree of life with over 70,000 species [2]; and the Living Liquid project, which created interactive visualizations of the micro and macroscopic life in the world's oceans [3]. These visualizations must address design challenges unique to museums and other informal learning contexts: the short time visitors spend at an exhibit; visitors who have little prior knowledge of the data or how it was collected; supporting multiple users for the majority of visitors who visit in groups; and, initiating and sustaining interest in the free-choice learning environment where there is no set sequence of exhibits and other competing attractions [4]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, logging has been applied to research contexts where real-time As curators and pedagogues aim to pursue the communicative and potential educational benefits of museum and science center environments in the digital age, increasing research attention is on measuring aspects such as attraction, engagement, holding power and dwell time of interactive exhibits [9][10][11][12]. Another developing area is probing how visitors actually use and interact with the digital platforms, and what the nature of interaction may eventually imply for learning [5,7,13].…”
Section: Research On Interactive Multi-touch Tables In Science Centermentioning
confidence: 99%
“…Recent research indicates that interactions afforded by modern technologies play a critical and highly relevant role in scientific meaning-making [4]. Moreover, recent work [5][6][7] also shows that analytical tools that track and log users' behavioural interactions can produce fine-grained information about how bodily processes of interaction could map onto processes of engagement and learning.…”
Section: Introductionmentioning
confidence: 99%
“…Research in public settings such as museums has often focused on the ways in which people approach and engage with touch table displays (e.g., (Hornecker 2008;Hinrichs and Carpendale 2011)) but there is also some evidence that use of interactive touch tables in museums can lead to deeper intellectual engagement than occurs otherwise. For example, Horn et al (2016) found that pairs of children (8-15 years old) who interacted with a touch table exhibit about evolutionary concepts showed learning gains over children who watched a video on the same topic. The authors observed that activation of relevant exhibit functions on the touch table, together with conversation about the information presented contribute to this deeper learning experience.…”
Section: Touch Table Research Areasmentioning
confidence: 99%